Responder
Here are the solutions for each equation:
1. **Problem (6):**
- \( x = -3 \)
- \( x = 0 \)
2. **Problem (8):**
- \( x = 1 \)
- \( x = 3 \)
3. **Problem (10):**
- \( x \approx 0.652946 \)
- \( x \approx 1.753639 \)
4. **Problem (12):**
- \( x = -5 - 2\sqrt{13} \)
- \( x = -5 + 2\sqrt{13} \)
5. **Problem (14):**
- \( x = -9 \)
- \( x = -8 \)
If you need more details on any of these solutions, let me know!
Solución
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{1}{x+1}-\frac{3x-1}{1-x}=2\)
- step1: Find the domain:
\(\frac{1}{x+1}-\frac{3x-1}{1-x}=2,x \in \left(-\infty,-1\right)\cup \left(-1,1\right)\cup \left(1,+\infty\right)\)
- step2: Multiply both sides of the equation by LCD:
\(\left(\frac{1}{x+1}-\frac{3x-1}{1-x}\right)\left(x+1\right)\left(1-x\right)=2\left(x+1\right)\left(1-x\right)\)
- step3: Simplify the equation:
\(2-3x-3x^{2}=-2x^{2}+2\)
- step4: Cancel equal terms:
\(-3x-3x^{2}=-2x^{2}\)
- step5: Move the expression to the left side:
\(-3x-3x^{2}-\left(-2x^{2}\right)=0\)
- step6: Subtract the terms:
\(-3x-x^{2}=0\)
- step7: Factor the expression:
\(-x\left(3+x\right)=0\)
- step8: Separate into possible cases:
\(\begin{align}&-x=0\\&3+x=0\end{align}\)
- step9: Solve the equation:
\(\begin{align}&x=0\\&x=-3\end{align}\)
- step10: Check if the solution is in the defined range:
\(\begin{align}&x=0\\&x=-3\end{align},x \in \left(-\infty,-1\right)\cup \left(-1,1\right)\cup \left(1,+\infty\right)\)
- step11: Find the intersection:
\(\begin{align}&x=0\\&x=-3\end{align}\)
- step12: Rewrite:
\(x_{1}=-3,x_{2}=0\)
Solve the equation \( \frac{-x^{2}+3 x+12}{x^{2}-3 x-4}+2=\frac{-1}{4-x} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{-x^{2}+3x+12}{x^{2}-3x-4}+2=\frac{-1}{4-x}\)
- step1: Find the domain:
\(\frac{-x^{2}+3x+12}{x^{2}-3x-4}+2=\frac{-1}{4-x},x \in \left(-\infty,-1\right)\cup \left(-1,4\right)\cup \left(4,+\infty\right)\)
- step2: Rewrite the fraction:
\(\frac{-x^{2}+3x+12}{x^{2}-3x-4}+2=-\frac{1}{4-x}\)
- step3: Multiply both sides of the equation by LCD:
\(\left(\frac{-x^{2}+3x+12}{x^{2}-3x-4}+2\right)\left(-x+4\right)\left(x+1\right)=-\frac{1}{4-x}\times \left(-x+4\right)\left(x+1\right)\)
- step4: Simplify the equation:
\(-x^{2}+3x-4=-x-1\)
- step5: Move the expression to the left side:
\(-x^{2}+3x-4-\left(-x-1\right)=0\)
- step6: Calculate:
\(-x^{2}+4x-3=0\)
- step7: Factor the expression:
\(\left(-x+3\right)\left(x-1\right)=0\)
- step8: Separate into possible cases:
\(\begin{align}&-x+3=0\\&x-1=0\end{align}\)
- step9: Solve the equation:
\(\begin{align}&x=3\\&x=1\end{align}\)
- step10: Check if the solution is in the defined range:
\(\begin{align}&x=3\\&x=1\end{align},x \in \left(-\infty,-1\right)\cup \left(-1,4\right)\cup \left(4,+\infty\right)\)
- step11: Find the intersection:
\(\begin{align}&x=3\\&x=1\end{align}\)
- step12: Rewrite:
\(x_{1}=1,x_{2}=3\)
Solve the equation \( \frac{-3 x+9}{x^{2}+x-2}=\frac{4}{x^{2}+6 x+8}+\frac{4}{1-x} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{-3x+9}{x^{2}+x-2}=\frac{4}{x^{2}+6x+8}+\frac{4}{1-x}\)
- step1: Find the domain:
\(\frac{-3x+9}{x^{2}+x-2}=\frac{4}{x^{2}+6x+8}+\frac{4}{1-x},x \in \left(-\infty,-4\right)\cup \left(-4,-2\right)\cup \left(-2,1\right)\cup \left(1,+\infty\right)\)
- step2: Multiply both sides of the equation by LCD:
\(\frac{-3x+9}{x^{2}+x-2}\times \left(-x^{2}-x+2\right)\left(x+4\right)=\left(\frac{4}{x^{2}+6x+8}+\frac{4}{1-x}\right)\left(-x^{2}-x+2\right)\left(x+4\right)\)
- step3: Simplify the equation:
\(-3x\left(-x-4\right)+9\left(-x-4\right)=36+20x+4x^{2}\)
- step4: Calculate:
\(3x^{2}+12x-9x-36=36+20x+4x^{2}\)
- step5: Simplify:
\(3x^{2}+3x-36=36+20x+4x^{2}\)
- step6: Move the expression to the left side:
\(3x^{2}+3x-36-\left(36+20x+4x^{2}\right)=0\)
- step7: Calculate:
\(-x^{2}-17x-72=0\)
- step8: Factor the expression:
\(-\left(x+8\right)\left(x+9\right)=0\)
- step9: Divide the terms:
\(\left(x+8\right)\left(x+9\right)=0\)
- step10: Separate into possible cases:
\(\begin{align}&x+8=0\\&x+9=0\end{align}\)
- step11: Solve the equation:
\(\begin{align}&x=-8\\&x=-9\end{align}\)
- step12: Check if the solution is in the defined range:
\(\begin{align}&x=-8\\&x=-9\end{align},x \in \left(-\infty,-4\right)\cup \left(-4,-2\right)\cup \left(-2,1\right)\cup \left(1,+\infty\right)\)
- step13: Find the intersection:
\(\begin{align}&x=-8\\&x=-9\end{align}\)
- step14: Rewrite:
\(x_{1}=-9,x_{2}=-8\)
Solve the equation \( \frac{2-x}{x+1}-\frac{2 x-4}{5-x}=-\frac{5 x-13}{x^{2}-4 x-5} \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{2-x}{x+1}-\frac{2x-4}{5-x}=-\frac{5x-13}{x^{2}-4x-5}\)
- step1: Find the domain:
\(\frac{2-x}{x+1}-\frac{2x-4}{5-x}=-\frac{5x-13}{x^{2}-4x-5},x \in \left(-\infty,-1\right)\cup \left(-1,5\right)\cup \left(5,+\infty\right)\)
- step2: Multiply both sides of the equation by LCD:
\(\left(\frac{2-x}{x+1}-\frac{2x-4}{5-x}\right)\left(-x+5\right)\left(x+1\right)=-\frac{5x-13}{x^{2}-4x-5}\times \left(-x+5\right)\left(x+1\right)\)
- step3: Simplify the equation:
\(14-5x-x^{2}=5x-13\)
- step4: Move the expression to the left side:
\(14-5x-x^{2}-\left(5x-13\right)=0\)
- step5: Subtract the terms:
\(27-10x-x^{2}=0\)
- step6: Rewrite in standard form:
\(-x^{2}-10x+27=0\)
- step7: Multiply both sides:
\(x^{2}+10x-27=0\)
- step8: Solve using the quadratic formula:
\(x=\frac{-10\pm \sqrt{10^{2}-4\left(-27\right)}}{2}\)
- step9: Simplify the expression:
\(x=\frac{-10\pm \sqrt{208}}{2}\)
- step10: Simplify the expression:
\(x=\frac{-10\pm 4\sqrt{13}}{2}\)
- step11: Separate into possible cases:
\(\begin{align}&x=\frac{-10+4\sqrt{13}}{2}\\&x=\frac{-10-4\sqrt{13}}{2}\end{align}\)
- step12: Simplify the expression:
\(\begin{align}&x=-5+2\sqrt{13}\\&x=\frac{-10-4\sqrt{13}}{2}\end{align}\)
- step13: Simplify the expression:
\(\begin{align}&x=-5+2\sqrt{13}\\&x=-5-2\sqrt{13}\end{align}\)
- step14: Check if the solution is in the defined range:
\(\begin{align}&x=-5+2\sqrt{13}\\&x=-5-2\sqrt{13}\end{align},x \in \left(-\infty,-1\right)\cup \left(-1,5\right)\cup \left(5,+\infty\right)\)
- step15: Find the intersection:
\(\begin{align}&x=-5+2\sqrt{13}\\&x=-5-2\sqrt{13}\end{align}\)
- step16: Rewrite:
\(x_{1}=-5-2\sqrt{13},x_{2}=-5+2\sqrt{13}\)
Solve the equation \( \frac{2 x^{2}-4 x}{x^{3}-3 x+2}=\frac{1}{x-2}-\frac{2}{1-x}+1 \).
Solve the equation by following steps:
- step0: Solve for \(x\):
\(\frac{2x^{2}-4x}{x^{3}-3x+2}=\frac{1}{x-2}-\frac{2}{1-x}+1\)
- step1: Find the domain:
\(\frac{2x^{2}-4x}{x^{3}-3x+2}=\frac{1}{x-2}-\frac{2}{1-x}+1,x \in \left(-\infty,-2\right)\cup \left(-2,1\right)\cup \left(1,2\right)\cup \left(2,+\infty\right)\)
- step2: Multiply both sides of the equation by LCD:
\(\frac{2x^{2}-4x}{x^{3}-3x+2}\times \left(x-1\right)\left(x^{2}+x-2\right)\left(-x+2\right)=\left(\frac{1}{x-2}-\frac{2}{1-x}+1\right)\left(x-1\right)\left(x^{2}+x-2\right)\left(-x+2\right)\)
- step3: Simplify the equation:
\(2x^{2}\left(-x+2\right)-4x\left(-x+2\right)=3x-6-x^{3}+5x^{2}-x^{4}\)
- step4: Calculate:
\(-2x^{3}+4x^{2}+4x^{2}-8x=3x-6-x^{3}+5x^{2}-x^{4}\)
- step5: Simplify:
\(-2x^{3}+8x^{2}-8x=3x-6-x^{3}+5x^{2}-x^{4}\)
- step6: Move the expression to the left side:
\(-2x^{3}+8x^{2}-8x-\left(3x-6-x^{3}+5x^{2}-x^{4}\right)=0\)
- step7: Calculate:
\(-x^{3}+3x^{2}-11x+6+x^{4}=0\)
- step8: Calculate:
\(\begin{align}&x\approx 1.753639\\&x\approx 0.652946\end{align}\)
- step9: Check if the solution is in the defined range:
\(\begin{align}&x\approx 1.753639\\&x\approx 0.652946\end{align},x \in \left(-\infty,-2\right)\cup \left(-2,1\right)\cup \left(1,2\right)\cup \left(2,+\infty\right)\)
- step10: Find the intersection:
\(\begin{align}&x\approx 1.753639\\&x\approx 0.652946\end{align}\)
- step11: Rewrite:
\(x_{1}\approx 0.652946,x_{2}\approx 1.753639\)
Here are the solutions for each of the equations provided:
### Problem (6)
\[
\frac{1}{x+1}-\frac{3 x-1}{1-x}=2
\]
**Solutions:**
- \( x_{1} = -3 \)
- \( x_{2} = 0 \)
### Problem (8)
\[
\frac{-x^{2}+3 x+12}{x^{2}-3 x-4}+2=\frac{-1}{4-x}
\]
**Solutions:**
- \( x_{1} = 1 \)
- \( x_{2} = 3 \)
### Problem (10)
\[
\frac{2 x^{2}-4 x}{x^{3}-3 x+2}=\frac{1}{x-2}-\frac{2}{1-x}+1
\]
**Solutions:**
- \( x_{1} \approx 0.652946 \)
- \( x_{2} \approx 1.753639 \)
### Problem (12)
\[
\frac{2-x}{x+1}-\frac{2 x-4}{5-x}=-\frac{5 x-13}{x^{2}-4 x-5}
\]
**Solutions:**
- \( x_{1} = -5 - 2\sqrt{13} \)
- \( x_{2} = -5 + 2\sqrt{13} \)
### Problem (14)
\[
\frac{-3 x+9}{x^{2}+x-2}=\frac{4}{x^{2}+6 x+8}+\frac{4}{1-x}
\]
**Solutions:**
- \( x_{1} = -9 \)
- \( x_{2} = -8 \)
If you need further assistance or explanations for any of these problems, feel free to ask!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución